Cultural intermediary in higher education based on ethical relation - Muna Yastuti Madrah; Suharko Suharko; Diana Dewi Sartika (Institute of Advanced Engineering and Science, 2024)
Preliminary studies on cultural intermediaries focused on social classes that mediate the production and consumption of culture. Therefore, this study determined the importance of the cultural intermediaries of migrant worker university students who popularize the values of higher education for the working class. Habitus and replication of meaning were used as analytical tools, with an alternative perspective proposed on cultural intermediaries using an ethical approach. The results showed that the cultural intermediary based on ethical relationships produces a new individual involvement of marginalized groups. Meanwhile, community relations with a similar social context are strengthened, enabling individuals to combine their allegiances and continuously generate values to suit certain social situations.